Pharmacogenetic testing to guide therapeutic decision‐making and improve outcomes for children undergoing anthracycline‐based chemotherapy. (11th May 2021) - Loucks, Catrina M.; Yan, Kevin; Tanoshima, Reo; Ross, Colin J. D.; Rassekh, Shahrad R.; Carleton, Bruce C.
Abstract: Anthracyclines are widely used as part of chemotherapeutic regimens in paediatric oncology patients. The most serious adverse drug reaction caused by anthracycline use is cardiotoxicity, a serious condition that can lead to cardiac dysfunction and subsequent heart failure. Both clinical and genetic factors contribute to a patient's risk of experiencing anthracycline‐induced cardiotoxicity. In particular, genetic variants in RARG, UGT1A6 and SLC28A3 have been consistently shown to influence an individual's risk of experiencing this reaction. By combining clinical and genetic risks, decision‐making can be improved to optimize treatment and prevent potentially serious adverse drug reactions. As part of a precision medicine initiative, we used pharmacogenetic testing, focused on RARG, UGT1A6 and SLC28A3 variants, to help predict an individual's risk of experiencing anthracycline‐induced cardiotoxicity. Pharmacogenetic results are currently being used in clinical decision‐making to inform treatment regimen choice, anthracycline dosing and decisions to initiate cardioprotective agents. In this case series, we demonstrate examples of the impact of genetic testing and discuss its potential to allow patients to be increasingly involved in their own treatment decisions.